Paprūdžių kapinyno kario kapo Nr. 24 geriamųjų ragų spektroskopiniai tyrimai - Ulozaitė, Regina (Archaeologia Lituana, 2008)
FTIR (Fourier Transform Infrared) spectral analysis was applied for identification of the residues of the white organic material from the horns bottom. The samples were squeezed between diamond windows and spectra obtained using AIM (Automated Infrared Microscope) with MCT detector. Spectra processed using IR Solution software, compared with those of known samples and data libraries and absorption bands identified. Though obtained results enable to make prediction that the substance in both horns could be residues of the alcoholic drink, probably mead, further research using modern physical methods of analyses are required.